Speed Controller Design using Hybrid Differential Evolution Algorithm-Particle Swarm Optimization for PSMS - Muhammad Aldo Setiawan; Herlambang Setiadi; Rodik Wahyu Indrawan; Rizki Putra Prastio (Journal of Advanced Technology and Multidiscipline, 2022)
The use of engines that motorized the world based on fossil fuel sources has led to many problems, such as air pollution, energy security, global warming, and climate change. To prevent further damage reducing the application of fossil fuel as a source of the motor is crucial. Hence, utilizing an electric motor could be the solution to reduce the application of motors based on fossil fuel. Among the number of electric motors, permanent magnet synchronous motor (PSMS) is becoming more popular due to their efficiency. However, the challenge here is how to design the controller of PSMS, especially the speed controller. Hence, this paper proposed a design of a speed controller of PSMS using a PI controller. The hybrid differential evolution algorithm-particle swarm optimization (DEA-PSO) is used to optimize the PI controller for better performance. From the simulation result, it is found that the proposed method can enhance the performance of PSMS.